DESIGN OF FISH WEIGHT MEASURING INSTRUMENT USING CONVEYOR FOR COASTAL FISHERMEN WITH ARDUINO INTEGRATION - Putra Andika; Erwinsyah Sipahutar; Rudi Arif Candra; Arie Budiansyah; Dirja Nur Ilham (Politeknik Aceh Selatan, 2025)
Indonesia is a country rich in natural resources including marine wealth when viewed from the geographical structure of Indonesia consists of thousands of islands spread from sabang to merauke. From natural conditions like this, the majority of Indonesian people's livelihoods are fishermen after farmers. But the technology used by our fishermen is still lagging behind so that fishermen cannot maximize the potential of Indonesian fisheries. So that applicative development is needed to make it easier for fishermen. In this study, the design of a tool to automatically count the number and weight of fish using an arduino-based load cell sensor was carried out. This automatic counter uses arduino uno as a processor of the data received and uses a load cell sensor as a detector of the number and weight of fish then the resulting output to the LCD. In this design, an hx711 module is also added which functions as a load cell data converter from analog to digital. The test data, the fish is placed on the conveyor belt that runs and is brought into the counter then the sensor will start to detect then give the command to the Arduino then output the results of the data to the LCD.